The Politics of Justification Party Competition and Welfare-State Retrenchment in Denmark and the Netherlands from 1982 to 1998 - Green-Pedersen, Christoffer (Changing Welfare States, 2002)
The Politics of Justification is an investigation of welfare retrenchment in Denmark and the Netherlands, 1982-1998. Welfare retrenchment is politically highly controversial, but still governments do retrench. This book argues that governments can implement retrenchment if they can achieve a party political consensus allowing them to frame retrenchment in a way that makes it seems justified to the electorate. In the Netherlands, such a consensus emerged in the mid 1980s due to the power of the CDA. It has allowed Dutch government to implement a number of welfare retrenchments. In Denmark, a consensus did not emerge until the Social Democratic Party re-entered government in 1993 explaining why the Danish welfare state has seen less retrenchment than the Dutch one. With its focus on the strategies of the political parties, the book differs from many other studies of the subject focusing on the role of political institutions.